2020
DOI: 10.1080/13696998.2020.1836923
|View full text |Cite
|
Sign up to set email alerts
|

Updated cost-effectiveness analysis of palivizumab (Synagis) for the prophylaxis of respiratory syncytial virus in infant populations in the UK

Abstract: Aims: Respiratory syncytial virus (RSV) is a common cause of respiratory infection in infants and severe infection can result in hospitalization. The passive immunization, palivizumab, is used as prophylaxis against RSV, however, use in the UK is restricted to populations at high risk of hospitalization. This study assesses the cost-effectiveness (CE) of palivizumab in premature infants with and without risk factors for hospitalization (congenital heart disease [CHD], bronchopulmonary dysplasia [BPD]). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…The data utilized in the model were from Greenough et al . 2004 [ 36 ], which are almost two decades old but arguably remain the best available source for utilities following RSVH and are used as the basis of many published cost-effectiveness and cost-utility assessments [ 28 , 45 , 69 ]. Similarly, the estimate of the disutility during RSVH is over 10 years old [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data utilized in the model were from Greenough et al . 2004 [ 36 ], which are almost two decades old but arguably remain the best available source for utilities following RSVH and are used as the basis of many published cost-effectiveness and cost-utility assessments [ 28 , 45 , 69 ]. Similarly, the estimate of the disutility during RSVH is over 10 years old [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming an even distribution of births across the year, infant weight at palivizumab administration was modelled using the growth algorithm described by Narayan et al . 2020 [ 45 ]. Based on this approach, the average cost of palivizumab in the base case was estimated to be €2,978 per 29–31wGA infant and €3,422 per 32–35wGA infant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…76–78 It is a passive immunization used as a prophylaxis. 82 It is provided by once-a-month intramuscular injection during the RSV infection season. It is indicated for prematurely born infants, and children with congenital heart disease to limit hospitalization.…”
Section: The Role Of Antiviral Inhibitorsmentioning
confidence: 99%
“…Thus, the impact of RSV disease reveals to have short-and long-term consequences and social implications that are difficult to calculate, which are often not included in cost-effectiveness analyses [62,68]. A recent study conducted in the UK showed that palivizumab prophylaxis is cost-effective in preventing severe RSV LRTI in a wider population than currently recommended in guidelines [69]. Narayan et al have found that palivizumab is cost-effective in premature infants born before 35 wGA without CHD or BPD aged <6 months at the start of the RSV season and in premature infants with CHD or BPD aged <2 years, if a mean of 3.7 doses rather than the five doses, is used.…”
Section: Palivizumabmentioning
confidence: 99%